Improved sizing of soot primary particles using mass-mobility measurements. Issue 2 (1st February 2016) - Dastanpour, Ramin; Rogak, Steven N.; Graves, Brian; Olfert, Jason; Eggersdorfer, Maximilian L.; Boies, Adam M.
ABSTRACT: The properties and impacts of aggregated aerosol particles (i.e., soot, metal oxide fumes) depend on their morphology, as characterized by fractal dimension, prefactor, and primary particle diameter. The morphology may be measured directly by time-consuming ex situ microscopy or rapid but indirect in situ methods. Previously, it was found that particle mass and mobility measurements could be used for the estimation of the primary particle diameter of zirconia aggregates, using plausible assumptions related to the fractal structure (specifically, prefactor and exponent ). Since the formation and growth of zirconia aggregates are different from carbon soot, here we compare primary particle diameters measured directly from transmission electron microscopy analysis of soot particles with the diameters estimated from mass–mobility measurements. Performing extensive measurements on soot emissions from two reciprocating engines over a range of operating conditions, we found that there are no universal values of and that can be used for all conditions. However, new optimized values of and are estimated here for soot particles. The variation of the primary particle diameter with particle size is also taken into consideration and is shown to be essential to obtain physically realistic results. Using optimized values of and, the average primary particle sizing error is reduced for all soot types. This suggests that with some calibration, in situ sizing of the primary particle diameter, using mass and mobility measurements, can provide useful accuracy. Copyright © 2016 American Association for Aerosol Research